A new pruning method for efficient broadcasting in ad hoc networks. (1st January 2011) - Rieck, Michael Q.; Dhar, Subhankar
This paper proposes a new multi-hop wireless broadcast method called k- shortest path pruning ( k- SPP). It is based on the dominant pruning method of Lim and Kim, and improves upon it in the context of certain routing protocols, such as the zone routing protocol. In this approach, every node must maintain as awareness of its k- hop neighbourhood, for some constant k ≥ 3. k- SPP dynamically discovers and exclusively uses forwarding paths having the property that every subpath of length k + 1 connects vertices that are a graph-theoretic distance k + 1 apart in the network graph. Experimental results demonstrate that k- SPP requires fewer transmissions than dominant pruning broadcasting.